FACTORS AFFECTING JOB SATISFACTION WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR APPROACH - Januari Ayu Fridayani (Management and Sustainable Development Journal, 2022)
The purpose of this study was to find out whether characteristics in the dimensions of Organizational Citizenship Behavior (OCB) influence job satisfaction. The study approach employed is quantitative, with data processed using SPSS 25. The study's sample technique is a saturation sampling technique that includes the entire population in the study. All 50 employees of business X were chosen as respondents for this study. To protect the privacy of the organization, the name of the organization cannot be disclosed in the publication of articles. The data processing test findings reveal that the five characteristics of OCB have an effect on job satisfaction at the same time. Meanwhile, altruism and civility have an effect on job satisfaction, as do the other three OCB dimensions namely civic virtue, conscientiousness and sportsmanship, have no effect on employee job satisfaction.